2021
DOI: 10.1016/j.spinee.2021.01.014
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β promotes disc degeneration and inflammation through direct injection of intervertebral disc in a rat lumbar disc herniation model

Abstract: BACKGROUND CONTEXT: Lumbar intervertebral disk herniation (LDH) is a common disease that causes low back pain, radiating leg pain, and sensory impairment. Preclinical studies rely heavily upon standardized animal models of human diseases to predict clinical treatment efficacy and to identify and investigate potential adverse events in human subjects. The current method for making the LDH model involves harvesting the nucleus pulposus (NP) from autologous coccygeal disks and applying to the lumbar nerve roots j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
(12 reference statements)
0
23
0
1
Order By: Relevance
“…In fact, studies also showed that the degeneration grade of IVD was aggravated by the accumulation of inflammatory cytokines. TNFα and IL-1β are the important inflammatory factors for intervertebral disc degeneration, which can induce intervertebral disc degeneration by reducing the anabolism of extracellular matrix proteins Hodges;James and Diwan, 2021;Hong;Jeon and Ha, 2021). TNF-α is able to inhibit the production of extracellular matrix and increase the expression of MMP-3, MMP-9, and MMP-13.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies also showed that the degeneration grade of IVD was aggravated by the accumulation of inflammatory cytokines. TNFα and IL-1β are the important inflammatory factors for intervertebral disc degeneration, which can induce intervertebral disc degeneration by reducing the anabolism of extracellular matrix proteins Hodges;James and Diwan, 2021;Hong;Jeon and Ha, 2021). TNF-α is able to inhibit the production of extracellular matrix and increase the expression of MMP-3, MMP-9, and MMP-13.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory factors (IL-1, IL-6, IL-8, and TNF-α) are key cytokines involved in aging and age-related diseases, whose expression levels are related to the severity of degeneration to a certain extent ( Krupkova et al, 2018 ; Zhang Y. et al, 2019 ; Kim et al, 2021 ). IL-1 has already been shown to be involved in the pathogenesis of intervertebral disc degeneration ( Phillips et al, 2013 ).…”
Section: Senescent Cells Play An Indispensable Role In Intervertebral...mentioning
confidence: 99%
“…p16 INK4a , known as a cell cycle suppressor, can inhibit cyclin-dependent kinases 4 and 6 (CDK4 and CDK6), causing stagnation of senescent cells at G1 phase ( Kim et al, 2021 ). The expression level of p16 INK4a increases in senescent cells; thus, p16 INK4a is always used as one of the commonly senescent cell markers (others: SA-β-gal, ki67) ( Krupkova et al, 2018 ; Ogrodnik, 2021 ).…”
Section: Senescent Cells Play An Indispensable Role In Intervertebral...mentioning
confidence: 99%
“…Patients with the lumbar intervertebral disc are often accompanied by the inflammatory stress response, and serum-related indicators will increase significantly. There are limited clinical studies on the evaluation of serumrelated indicators of dual-channel endoscopic lumbar intervertebral disc discectomy for LDH patients (20). In this study, dual-channel endoscopic lumbar discectomy was used to treat LDH patients, and IL-6, IL-10, PGE2 and other indicators were used to evaluate the efficacy of surgical treatment, as discussed below.…”
Section: The Evaluation Value Of Il-6 Il-10 and Pge2 In The Postopera...mentioning
confidence: 99%